An integrative review on unveiling the causes and effects of decision fatigue to develop a multi-domain conceptual framework - Choudhury, Nurul Ahad; Saravanan, Pratima (Frontiers in Cognition, 2026)
Decision fatigue leads to reduced efficiency in the rate and quality of decisions. Thus, examining the reasons behind decision fatigue and comprehending its influence on decision-making in various professional domains is pivotal to improving the decision-making process. The aim of this integrative review is to investigate the causes and effects of decision fatigue from the existing literature and develop a framework that can be applied across different domains. A comprehensive literature search in three databases identified 1,027 articles on decision fatigue. After screening the articles using Integrative reviews and Meta-Analysis (PRISMA) and Joanna Briggs Institute (JBI) appraisal methods, 23 articles investigating decision fatigue across various domains were selected. The selected articles were investigated through root cause analysis and thematic synthesis. Findings revealed ten causes of decision fatigue, which were classified as individual, organizational, and external causes, and four primary effects and seven secondary effects of decision fatigue. Using these findings, a conceptual framework that offers a comprehensive understanding of decision fatigue across diverse domains was developed. Knowledge of what causes decision fatigue can help optimize the decision-making process for decision makers. This study contributes to the concept of decision fatigue within organizational settings to enhance organizational behavior, psychology, and offers implications for improving decision-making processes in diverse professional domains. The findings can help develop interventions to mitigate decision fatigue and improve overall decision-making.